Critical reflection in midwifery practice: the protection motivation theory. Issue 3 (3rd May 2016) - Fenech, Giliane
Abstract: Background: The aim of this paper is to shed light on the notion of fear and inter-personal working relationships, and to promote safe midwifery practice, by critically reflecting on our practice and being aware of fear appeals and the protection motivation theory (PMT). Theory: PMT provides a general account of the impact of persuasive communication, emphasising the cognitive processes that mediate behaviour change and questions whether 'fear appeals' could influence behaviour. Discussion: It is possible that when a midwife decides on a particular care pathway, she determines the degree and perception of the four elements of the PMT; severity, vulnerability, response-efficacy and self-efficacy. If the midwife decides that both the degree of severity and her perception of vulnerability are high, whereas response and self-efficacy perceptions are low, she will probably decide against her original care pathway. For the PMT to be used safely, an appropriate judgement call is required and is based on full understanding of the situation, effective communication with the multidisciplinary team, full knowledge of the proposed care, and competence and confidence in the proposed care. Conclusion: By critically reflecting on their practice and using the PMT, the author believes that midwives will be able to work in partnership with obstetricians to provide safe and effective care within their sphere of practice and in the absence of fear.